Complete genome of the extensively antibiotic-resistant GC1 Acinetobacter baumannii isolate MRSN 56 reveals a novel route to fluoroquinolone resistance. (11th April 2022) - Harmer, Christopher J; Lebreton, Francois; Stam, Jason; McGann, Patrick T; Hall, Ruth M
Abstract: Objectives: To examine the causes of antibiotic resistance in the extensively resistant global clone 1 (GC1) Acinetobacter baumannii isolate MRSN 56 recovered at a US military treatment facility. Methods: MRSN 56 was sequenced using MinION (Oxford Nanopore) and the reads combined with available Illumina MiSeq data using Unicycler. Acquired resistance genes were identified using ABRicate and their environment examined. ISAba1 and ISAba125 copies were located. Results: MRSN 56 is ST1 IP :ST231 Ox :KL1:OCL1 and the complete genome includes four small plasmids, none of which carry resistance genes. The acquired resistance genes were found at four locations in the chromosome in addition to AbaR28 ( aphA1, aacC1, aadA1, sul1 ) in comM . Tn 2006 ( oxa23, carbapenem resistance) was both in AbaR4 and alone elsewhere. Two copies of Tn 7 ( dfrA1, sat, aadA1 ) were identified. One was associated with a 22 852 bp adjacent segment [ tetA (B), sul2 ] derived from the AbGRI1 island, and this novel configuration was designated Tn 7+ . Tn 7+ was incorporated in the position preferred by Tn 7, downstream of glmS, by transposition using a sequence in AbGRI1 resembling the Tn 7 terminal inverted repeats. Tn 7 was found at a secondary site. Fluoroquinolone resistance appears to involve a mutation in gyrA combined with inactivation by ISAba1 of the marR gene in the mar operon and constitutive expression of marA from the promoter internal to ISAba1. Conclusions: MRSN 56 represents a new sublineage of GC1 lineage 1 with novel features that had not been detected previously. The involvement of the mar operon in fluoroquinolone resistance has not been noted previously.